The Impact of Area-Limited Skin Burns in the Severity of the Burn Disease and Outcome of Inhalation Injury - E. A. Zhirkova; T. G. Spiridonova; E. I. Eliseenkova; A. V. Sachkov; V. S. Borisov; P. A. Brygin; A. M. Gasanov (Неотложная медицинская помощь, 2022)
Introduction Inhalation injury (ini) makes burn disease more severe. However, it remains unexplored what is the minimum area of the burn that can significantly aggravate of the course of ini.The objective was to compare the incidence of acute respiratory failure (arf), pneumonia, and mortality between patients with ini and ini with superficial skin burns up to 3% total body surface area (tbsa).Material and methods 125 patients with ini and i–ii degree skin burns up to 3% tbsa were allocated into 4 groups: ini without skin burns, ini with burns up to 1% tbsa, up to 2%, and up to 3% tbsa.Results In the group with ini and skin burns up to 2%, the number of arf, pneumonia cases, and deaths did not statistically significantly differ from the ini group, however in group of ini and burns of more than 2% tbsa, there were more of those complications.Conclusion Skin burns of i–ii degree over 2% tbsa increase the incidence of acute respiratory failure, pneumonia, and death in patients with ini.